The Economics of Audit Production: What Matters for Audit Quality? An Empirical Analysis of the Role of Midlevel Managers within the Audit Firm - Aobdia, Daniel; Choudhary, Preeti; Newberger, Noah (The Accounting Review, 2024)
ABSTRACT As audits of public companies are labor intensive, require a variety of team members, and involve year-round work, practitioners and academics have increasingly focused on identifying audit production factors that drive audit quality. Using proprietary data, we analyze the cost-benefit tradeoffs of two audit production characteristics, client expertise and the relative amount of auditing done during the early phases of the audit, and find that both are associated with more effective audits and higher fees. We analyze whether the influence of these characteristics varies across audit team members. We find that middle manager production characteristics explain audit effectiveness and higher fees and relatively more so than those of lead/review partners. These results extend the literature and practitioner discussions about drivers of audit quality by highlighting the importance of middle management, which, to our knowledge, has largely been overlooked by the archival audit literature and regulatory guidance on audit quality indicators. Data Availability: This paper exploits proprietary PCAOB data. Data descriptions are available in the text. JEL Classifications: D20; D22; J24; L23; M11; M4; M42; M48.